Penerapan Model Contextual Teaching and Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa di SMKN 6 Medan: Penelitian - Agnes Putri Siahaan; Tuti Sriwedari; Choms Gary Ganda Tua Sibarani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Student activities and learning outcomes are two things that are interrelated and support each other to achieve an effective learning process. The study aims to describe the effectiveness of the application of Contectual Teaching and Learning model in improving learning activities and outcomes in the adjustment journal material. The study was conducted using a classroom action research method implemented in two cycles. In each cycle, it is divided into two meetings consisting of four stages, namely : planning, action, observation, and reflection. The subjects of the study were 36 students of grade XI AKL 1 SMKN 6 Medan. the data collection techiques used were observation, documentation, and test. The results showed that the average percentage of student learning activities increased from 36,11% in cycle I to 86,11% in cycle II. An increase also occurred in learning outcomes from 73,61% in cycle I to 93,05% in cycle II. It can be concluded that the application of the Contextual Teaching and Learning model is effective in improving student activities and learning outcomes, especially in understanding the accounting material for adjustment journal entries.